2015
DOI: 10.1002/2015ja021343
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for determining Substorm Onsets and Phases from Indices of the Electrojet (SOPHIE)

Abstract: We present a new quantitative technique that determines the times and durations of substorm expansion and recovery phases and possible growth phases based on percentiles of the rate of change of auroral electrojet indices. By being able to prescribe different percentile values, we can determine the onset and duration of substorm phases for smaller or larger variations of the auroral index or indeed any auroral zone ground‐based magnetometer data. We apply this technique to the SuperMAG AL (SML) index and compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(256 citation statements)
references
References 84 publications
(181 reference statements)
10
246
0
Order By: Relevance
“…Forsyth et al . [] found that the expansion phase onsets determined using the 75th percentile gave good agreement with existing auroral‐based [ Frey and Mende , ; Liou et al ., ] and magnetometer‐based [ Newell and Gjerloev , ] substorm onset lists. Thus, we use this percentile for all phase identifications in this study.…”
Section: Instrumentation and Methodologysupporting
confidence: 78%
“…Forsyth et al . [] found that the expansion phase onsets determined using the 75th percentile gave good agreement with existing auroral‐based [ Frey and Mende , ; Liou et al ., ] and magnetometer‐based [ Newell and Gjerloev , ] substorm onset lists. Thus, we use this percentile for all phase identifications in this study.…”
Section: Instrumentation and Methodologysupporting
confidence: 78%
“…Here we use the criterion that the standard deviation of D p during the 90 min (60 min preceding and 30 min following) is smaller than 30% of the average D p . The second step is to further select the isolated substorm events from the IMF southward turning events. The SuperMAG SML index (Gjerloev, ) and substorm onset lists from Newell and Gjerloev () and Forsyth et al () (a specified expansion phase threshold of 50%) are employed in the selection. The preceding period should be with average value of SML greater than −100 nT in 1 h, and there should be no substorm onsets listed by Newell and Gjerloev () and Forsyth et al ().…”
Section: Observations For Equatorial Plasma Pressure Variationsmentioning
confidence: 99%
“…In Yakymenko and Borovsky [] this SML‐jump method of identifying substorm onsets was compared with other methods: basically, the SML‐jump method identifies large, nontransient events and the occurrence statistics of these events agrees with the occurrence statistics of substorms identified by energetic‐particle injections into geosynchronous orbit [e.g., Borovsky et al , ; Borovsky and Yakymenko , ] and with prior schemes that identified substorms with jumps in the AL index [e.g., Prichard et al , ]. The SML‐jump events are statistically different from the events chosen by the Substorm Onsets and Phases from Indices of the Electrojet (SOPHIE) algorithm [ Forsyth et al , ] and the events denoted as MPB events [ Chu et al , ], with the SOPHIE and MPB events being smaller and much more numerous [ Yakymenko and Borovsky , ].…”
Section: Creating the Indicesmentioning
confidence: 99%
“…Second, there is not an agreed‐upon method of determining the onset time of a substorm [ Kepko et al , ; Nishimura et al , ; Lui , ; Borovsky and Yakymenko , ]. Third, there is confusion about substorm onsets versus substorm activations (reactivations and intensifications) [ Kisabeth and Rostoker , ; Forsyth et al , ; McPherron and Chu , ; Yakymenko and Borovsky , ]. Fourth, whatever the data source for creating a substorm index, a continuous data coverage is necessary.…”
Section: Introductionmentioning
confidence: 99%